Research on the brand image of iOS and Android smart phone operating systems based on mixed methods - Hu, Weifeng; Hao, Tianyun; Hu, Yue; Chen, Hui; Zhou, Yi; Yin, Wantong (Frontiers in Psychology, 2023)
To analyze the differences in system functions, interaction behaviors and user experience between iOS and Android smart phone operating system, and then study the differences in their brand images, so as to provide theory and research method for shaping corporate brand images from the perspective of product interaction design. This study was divided into three stages. In the first stage, the functional information architecture of iOS and Android smart phone operating system are studied comparatively by using information visualization methods. In the second stage, the brand image differences between the two systems at the explicit, behavioral and semantic levels are analyzed comparatively by building the "explicit - behavioral - semantic" product brand gene model. In the third stage, the functions of "setting alarm clock", "sharing pictures" and "modifying passwords" were selected for interactive behavior analysis. First, analyze the user experience of the three system functions from the perspective of interaction process and information architecture, and present the analysis results using the method of information visualization.; Secondly, the user experience and brand image differences between the two systems are analyzed by setting up manipulation task experiments. The brand images of iOS and Android systems are similar in conciseness, clearness and efficiency; In terms of uniqueness, iOS system is more unique, while Android system has stronger applicability. This study constructs an "explicit-behavior-semantic" brand gene model to create a unique product brand image for software products such as operating systems through interactive design, so as to solve the problem of product brand image homogeneity caused by the convergence of function and interaction design.